Concepções de língua(gem) que integram o ideário pedagógico de uma professora e de seus alunos na sala de aula de português-LE - Souza, Aline Gomes (2016)
This thesis presents the results of a qualitative case study carried out in a Portuguese as a Foreign Language (Portuguese-FL) classroom with exchange students attending Universidade Federal de Goiás (UFG). Its general aim was to verify which language concepts underlie teacher-student dialogical interactions in the classroom. As regards specific aims, this study sought to (i) identify and analyse which language concepts support the teacher’s pedagogical approach during lessons to this particular group of students; (ii) understand students’ perceptions concerning what it means to learn and teach a foreign language, in this case Portuguese; (iii) gather evidence of change in the teacher’s view on language and on what it means to teach and learn a foreign language, as well as verify to what extent this change is influenced by students’ perceptions. To achieve these aims, this thesis is grounded in the qualitative principles of case studies, considering that this approach allows for a holistic and naturalistic view of the context and of participants’ actions, behaviour, and interactions regarding the problematics at hand. The theoretical framework covers Chomsky’s (1957, 1959) concept of grammatical competence and Hymes’ (1986) concept of communicative competence, as well as the works of Bakhtin/Volochínov (2009) and Bakhtin (2012b) concerning the constitutive dialogic principle of language. Results show that three concepts underlie the teacher’s pedagogical reasoning over the course of her teaching internship in the classroom researched. The first, formalist or structuralist, views language as a system of linguistic structures which interact to produce meanings. From this perspective, teaching/learning a FL equates to teaching/learning its forms. The second concept, interactionist or communicativist, sees language as an instrument for communicating and expressing meaning. In this sense, teaching/learning a FL equates to teaching/learning to use it for communication. The third concept, dialogic, addressed in the second part of the analysis, regards language as the locus for social/interpersonal interactions. Teaching/learning a FL is, therefore, a dialogic process.